Zero Waste Campus A Framework And Digital Learning Module For Sustainable Environmental Practices In Higher Education Institution - Nalikant, Mayawi Baba (2024)
The global rise in population and living standards has led to increased waste production, a significant issue in Malaysian universities where existing waste management methods such as recycling and reusing are inadequate. Guided by Saunders Research Onion methodology, this study examines the awareness and participation of Malaysian university communities in zero-waste initiatives focused on waste prevention. Utilizing a mixed-method approach with focus group discussions and in-depth interviews, the research identified ten key factors influencing Pro-Environmental Behaviour: personal experiences, environmental education, social technology, social responsibility, self-awareness, reinforcement contingencies, policy, leadership, community engagement, and environmental goals. These factors were synthesized into a framework that integrates an adapted Knowledge, Attitudes, Practices, Values, and Technology (KAPVT) theoretical framework with Kollmuss and Agyeman's PEB Model, Theory of Planned Behavior, and Value-Belief-Norm Theory, providing a comprehensive view of PEB. Structural Equation Modelling - Confirmatory Factor Analysis validated the relationships within this expanded framework using survey data from 393 respondents across three Malaysian universities. The findings demonstrated significant positive correlations between factors, leading to the creation of a digital Zero-Waste Campus Learning Module to promote sustainable practices. This provides a robust framework for enhancing national waste reduction strategies and advancing campus sustainability.